Protophilic solvent-impelled quasi-catalytic CO2 valorization to formic acid and N-formamides - Wu, Hongguo; Li, Hu; Zhao, Wenfeng; Sudarsanam, Putla; Yang, Song (Fuel, 2022)
As a low-price and luxuriant C1 sustainable resource, CO2 has the privilege of synthesizing hydrogen carriers and valuable chemicals. However, expensive metallic and organic catalysts are often indispensable for going on wheels of the relevant reaction processes. In this work, a protophilic solvent-impelled quasi-catalytic system was developed for efficient synthesis of formic acid and various N-formamides with high yields of 76-94% via reductive CO2 functionalization under mild reaction conditions (50 ?). Direct activation of the liquid hydrosilane toward the reduction of CO2 enabled by DMSO with optimum basicity/protophilicity is the predominant reaction route among the examined interaction models, while carbonic acid potentially derived from excessive CO2 and residual water inhibits the reaction, as explicitly disclosed by theoretical calculations and isotope labeling experiments. In addition, the in situ formed O-formyl species is conductive to the cascade CO2 reduction steps, which remarkably facilitated the overall quasi-catalytic upgrading process.
Keywords: CO2 utilization; Formic acid; Green energy; Nitrogenous chemicals; Quasi-catalysis